The World's Youngest Cadaveric Kidney Transplant: Medical, Surgical and Ethical Issues. Issue 12 (December 2016) - Daar, Abdallah S.; Al Lawati, Nabil Mohsin
Abstract : Background: We report here the first successful transplant from a preterm cadaveric donor. This was performed in November 1994. The donor, who had been born at about 33 weeks of gestation, was diagnosed as having agenesis of the corpus callosum. The transplant was carried out 10 days after the donor's birth. The recipient was a 17-month-old boy with a diagnosis of Denys-Drash syndrome (WT1 mutation). Method: We describe and analyze the ethical, social, cultural, medical and surgical issues encountered and how these were addressed. The major issue of determining death in a beating heart, very young donor was dealt with in the absence of worldwide experience and guidelines. Results: The transplanted recipient has lived with the grafted pair of kidneys for more then 22 years. He has led a relatively normal life. Conclusions: It is possible for immature preterm deceased donor kidneys to be transplanted into a 17-month-old recipient and for the grafted kidneys to grow with the recipient and function for 22 years. There were challenges in ethically determining the death of the donor, in surgical techniques to obviate potential surgical complications, and in postoperative care of the recipient, but these were managed successfully.